Medicine and fairy tales - Ramšak, Mojca (Acta Histriae, 2022)
Fairy tales are fascinating fantasies, but they also gave people a better understanding of serious issues such as illness, injury, and even death. The results of the analysis of a large corpus of a total of 1512 published fairy tales, legends, and other documentary prose about Pohorje, most of which date back to the 19th and the first half of 20th centuries, and whose origins were in a time when diseases were ubiquitous and poorly understood, show that the theme of health and disease rarely appear in these sources, however, when they do mention it, they refer specifically to the living conditions of people in the Pohorje Mountains, epidemics, social diseases, mental illnesses, congenital deformities, and ideas about the relationship between disease, the human body, and supernatural forces. One of the reasons for such explanations is the widespread absence of doctors in this hilly area.
Keywords: alkoholizem; bolezen; medicinska humanistika; narativna medicina; Pohorje; poškodbe; pravljica; Slovenija; socialne bolezni; zdravje; zgodovina medicine